2014
DOI: 10.1007/s00213-014-3682-3
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and dopamine differentially affect appetitive and aversive general Pavlovian-to-instrumental transfer

Abstract: These results demonstrate a differential involvement of serotonin and dopamine in motivated behavior. They suggest that reductions in serotonin enhance the motivational influence of aversive stimuli on instrumental behavior and do not affect the influence of appetitive stimuli, while reductions in dopamine diminish the influence of appetitive stimuli. No conclusions could be drawn about how dopamine affects the influence of aversive stimuli. The interplay of both neurotransmitter systems allows for flexible an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 73 publications
4
46
3
Order By: Relevance
“…Some evidence in humans suggests that the dopamine and serotonin systems play opposing or at least complementary roles 23,24,[42][43][44] . In this view, the serotonin system primarily underpins punishment processing whereas the dopamine system primarily underpins reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence in humans suggests that the dopamine and serotonin systems play opposing or at least complementary roles 23,24,[42][43][44] . In this view, the serotonin system primarily underpins punishment processing whereas the dopamine system primarily underpins reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…appetitive cues promote active responding (appetitive PIT), whereas aversive cues increase behavioural inhibition (aversive PIT; Davis and Wright, 1979; Huys et al, 2011). Enhanced dopamine increases appetitive PIT (Wyvell and Berridge, 2000), while appetitive PIT is lowered when striatal dopamine is reduced (Dickinson et al, 2000; Hebart and Gläscher, 2015; Lex and Hauber, 2008). Striatal dopamine has also been linked to controlling aversively motivated behaviour (Faure et al, 2008; Lloyd and Dayan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with a contribution of the amygdala in representing motivational control of instrumental responses (Baxter and Murray, 2002; Balleine and Killcross, 2006). Previous studies mainly demonstrated amygdala's involvement in mediating between S-O and R-O associations by using the Pavlovian-to-Instrumental Transfer paradigm (Huys et al, 2011;Prévost et al, 2012;Hebart and Gläscher, 2015), where the two associations are learned separately and their interaction is examined afterward during extinction. However, our subjects had no prior training for associating the stimulus to primary reward.…”
Section: Amygdala's Involvement In the Stimulus And Reward Learningmentioning
confidence: 99%
“…However, there are two sources of uncertainty in our task: one associated with the stimulus likelihood and the other associated with the reward probabilities. Both human and animal studies have demonstrated the amygdala's engagement in learning environmental contingencies (Hsu et al, 2005;Herry et al, 2007;Madarasz et al, 2016), showing greater activation of the amygdala in response to stimuli associated with greater degrees of uncertainty or unpredictability. Thus, the greater amygdala response in the biased condition of our task may reflect a greater amount of reward uncertainty due to the conflict between stimulus and reward likelihood.…”
Section: Amygdala's Involvement In the Stimulus And Reward Learningmentioning
confidence: 99%